2022
DOI: 10.1101/2022.06.20.496825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Purely STDP-based assembly dynamics: stability, learning, overlaps, drift and aging

Abstract: Memories may be encoded in the brain via strongly interconnected groups of neurons, called assemblies. The concept of Hebbian plasticity suggests that these assemblies are generated through synaptic plasticity, strengthening the recurrent connections within select groups of neurons that receive correlated stimulation. To remain stable in absence of such stimulation, the assemblies need to be self-reinforcing under the plasticity rule. Previous models of such assembly maintenance require additional mechanisms o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
0
10
1
Order By: Relevance
“…Another way to promote bidirectional connections is using a symmetric STDP rule which has dominant depression (Manz & Memmesheimer, 2022) or without any LTD (Ravid Tannenbaum & Burak, 2016). In this setting, synaptic weights grow linearly with the pre‐ and postsynaptic rates, and further increase bidirectionally when neurons fire close in time, regardless of the firing order.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another way to promote bidirectional connections is using a symmetric STDP rule which has dominant depression (Manz & Memmesheimer, 2022) or without any LTD (Ravid Tannenbaum & Burak, 2016). In this setting, synaptic weights grow linearly with the pre‐ and postsynaptic rates, and further increase bidirectionally when neurons fire close in time, regardless of the firing order.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in the sensory deprived zebrafish larvae have shown that assemblies can also form without external input, only due to network‐intrinsic activity (Pietri et al., 2017). Such assembly formation without structured input has been obtained in computational models with different forms of STDP based on the two frameworks discussed above: either mainly driven by the rate contribution (zero‐order motif) (Babadi & Abbott, 2013; Burkitt et al., 2007; Gilson et al., 2009b; Ocker et al., 2015; Ocker & Doiron, 2019), or by higher‐order motifs arising from internal correlation structure with the rate contribution minimised (Montangie et al., 2020; Ocker et al., 2015; Ocker & Doiron, 2019; Ravid Tannenbaum & Burak, 2016), or a combination thereof (Manz & Memmesheimer, 2022). When network‐intrinsic correlations contribute significantly to assembly formation, symmetry breaking in the network develops either due to random fluctuations in an otherwise symmetric network, or due to an initial bias in the connectivity matrix (Ocker & Doiron, 2019; Triplett et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanisms underlying the emergence of drift and its relevance for the neural computation are not known. Drift is often thought to arise from variability of internal states [2], neurogenesis [1,9] or synaptic turnover [10] combined with noise [11,12]. On the other hand, excitability might also play a role in memory allocation [13][14][15][16], so that neurons having high excitability are preferentially allocated to memory ensembles [16][17][18].…”
Section: Introductionmentioning
confidence: 99%